Ice cream cones - Nelson, Penelope, 1994- (2019)
This book introduces readers to the history and culture associated with ice cream cones, and it shows them they can make this favorite food at home. Vivid photographs and easy-to-read text aid comprehension for early readers. Features include a table of contents, an infographic, fun facts, Making Connections questions, a glossary, and an index. QR Codes in the book give readers access to book-specific resources to further their learning.
Ice cream -- Cones -- Waffle and cake -- How to make ice cream.
Includes index.
Ages 4-8
Keywords: Ice cream cones -- Juvenile literature